Multiple sclerosis associated genetic variants of CD226 impair regulatory T cell function. (10th September 2015) - Piédavent-Salomon, Melanie; Willing, Anne; Engler, Jan Broder; Steinbach, Karin; Bauer, Simone; Eggert, Britta; Ufer, Friederike; Kursawe, Nina; Wehrmann, Sabine; Jäger, Jan; Reinhardt, Stefanie; Friese, Manuel A.
Abstract : A variant of the CD226 gene predisposes to multiple sclerosis. Piédavent-Salomon et al. show that CD226 expression is reduced in regulatory T cells (Treg) of CD226 risk-haplotype carriers and patients with multiple sclerosis, compared to healthy protective-haplotype carriers. Treg suppressive ability is reduced in patients, risk-haplotype carriers and Cd226 -deficient mice. Abstract : Abstract : Recent association studies have linked numerous genetic variants with an increased risk for multiple sclerosis, although their functional relevance remains largely unknown. Here we investigated phenotypical and functional consequences of a genetic variant in the CD226 gene that, among other autoimmune diseases, predisposes to multiple sclerosis. Phenotypically, effector and regulatory CD4 + memory T cells of healthy individuals carrying the predisposing CD226 genetic variant showed, in comparison to carriers of the protective variant, reduced surface expression of CD226 and an impaired induction of CD226 after stimulation. This haplotype-dependent reduction in CD226 expression on memory T cells was abrogated in patients with multiple sclerosis, as CD226 expression was comparable to healthy risk haplotype carriers irrespective of genetic variant. Functionally, FOXP3-positive regulatory T cells from healthy carriers of the genetic protective variant showed superior suppressive capacity, which was again abrogated in multiple sclerosis patients. Mimicking the phenotype of human CD226 genetic risk variant carriers, regulatory T cells derived from Cd226 -deficient mice showed similarly reduced inhibitory activity, eventually resulting in an exacerbated disease course of experimental autoimmune encephalomyelitis, the animal model of multiple sclerosis. Therefore, by combining human and mouse analyses we show that CD226 exhibits an important role in the activation of regulatory T cells, with its genetically imposed dysregulation impairing regulatory T cell function.